Formulasi dan Uji Sifat Fisik Sediaan Lulur Krim dari Ekstrak Etanol Daun Sirsak (Annona muricata L.) serta Penentuan Aktivitas Antioksidannya - Hakim, Zainur Rahman; Meliana, Dewi; Utami, Pri Iswati (JSFK (Jurnal Sains Farmasi & Klinis), 2020)
The ethanolic extract of soursop leaves (Annona muricata L.) is reported as an antioxidant agent with an IC50 value of 14.48 Âµg/mL. This research aimed to examine physical characteristics and investigate the antioxidant activity of the ethanolic extract of soursop leaves in a scrub cream. Soursop leaves powder was extracted with 70% ethanol and formulated as scrub cream at the concentration of 1.4%, 2.8%, and 4.2%, then evaluated for physical characteristics. The antioxidant activity was evaluated using DPPH (1.1-diphenyl-2 picrylhydrazyl) method. The result showed that the scrub cream at all concentrations tested fulfilled all physical characteristics required for good topical preparations. These included organoleptic, homogeneity, viscosity, pH, spreadability, and adhesion. The IC50 value of the scrub cream at the concentration of 1.4%, 2.8 %, and 4.2% were 30.72, 26.82, and 24.03 Âµg/mL, respectively. The IC50 values indicated that the scrub creams exhibit radical scavenging activities which categorized as strong activity antioxidants.